# Answer to Question #11462 in Trigonometry for safanussrath

Question #11462

prove that

a)cos(90-/theta)cosec(90-/theta)=tan/theta

a)cos(90-/theta)cosec(90-/theta)=tan/theta

Expert's answer

cos(90-/theta)cosec(90-/theta)=tan/theta

First of all, cos(90-/theta)=sin(/theta)

also cosec(90-/theta)=1/sin(90-/theta)=1/cos(/theta)

So we have& cos(90-/theta)cosec(90-/theta)= sin(/theta)/cos(/theta)=tan/theta

First of all, cos(90-/theta)=sin(/theta)

also cosec(90-/theta)=1/sin(90-/theta)=1/cos(/theta)

So we have& cos(90-/theta)cosec(90-/theta)= sin(/theta)/cos(/theta)=tan/theta

## Comments

## Leave a comment